MODEL SISTEM PENGOLAHAN DATA PENGADUAN KARYAWAN UNTUK MENGUKUR KEPUASAN PELAYANAN DALAM MENINGKATKAN KINERJA PERUSAHAAN - Junaidi Junaidi; Siti Euis Iyana Nurlia; Fira Arbaimaniar Nurul (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
Companies that are engaged in industry, currently continue to experience growth, along with increasing demand, this is certainly followed by an increase in the number of employees to reach tens of thousands, so that the company can reach the specified production targets every day. Management of a company with this number of employees is not easy, this can be seen from the high number of employee complaints that have an impact on company performance. To maintain employee performance, companies are demanded to be able to deal with every employee complaint quickly and accurately. The above problems certainly require a system that is able to measure the satisfaction of company services to employees, so that the company's performance is maintained well, besides that the system that has been running in the form of complaints is considered ineffective and inefficient, because it results in high costs for paper form preparation, not to mention the difficulties in recapitulation of complaints, this is the cause of the slow realization of actions against employee complaints and frequent errors of action due to inaccurate reports. This problem can be overcome with a computerized system, so it is expected to be able to create a recapitulation quickly, so that actions can be taken appropriately. By using various data collection and analysis methods, the design method includes usecase, activity, sequences and class diagrams, to produce an integrated system so that it can measure employee satisfaction and improve company performance.